Perencanaan Ulang Tata Letak Fasilitas Produksi Dengan Metode Algoritma Craft - Sahroni, S (Jurnal Teknik Industri, 2003)
The PT. ERATEX DJAJA. Tbk. Probolinggo, on the weaving department had often the matedal disturbance and retum flow of the moying material doe to the position of the department isn't suitable, so that needs arrangement the layout and production facilities that emcient and flexibility in the weaving deparhnent to avoid of the backtracking that can added the length of the moving distance ofmaterial, so that will drop down the productivity. Anangemenl and production facilities layout arrangemâ‚¬nt using CRAFT algorithm method to know the activity of production process from part one to another part, include the moving distance of handling material frequency. Compare the suggestion layout with the fist layout, then can to determine the advantagâ‚¬ layout by the base method. From the analysis we can know on the suggestion layout have long distance 10,82% conceming fist layout. Backtracking of the material haadling occur 6 time, therc are reducing 15,86% from the fist layout. The moving cost efficiency 2,05% occur fist layout.